2021
DOI: 10.1007/s00393-021-00976-7
|View full text |Cite
|
Sign up to set email alerts
|

Patientensicherheit in der Rheumatherapie

Abstract: Zusammenfassung Hintergrund Methotrexat (MTX) ist das das am häufigsten verordnete krankheitsmodifizierende Antirheumatikum. Ein regelmäßiges Labormonitoring wird empfohlen, um Nebenwirkungen wie Hepatotoxizität und Myelotoxizität sowie MTX-Toxizität-begünstigende Zustände wie eingeschränkte Nierenfunktion früh zu erkennen. Zudem wird eine prophylaktische Folsäuregabe empfohlen. Diese Arbeit untersucht, ob die empfohlene Kontrolluntersuchungen und Folsäureverordnungen während der MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…During long-term therapy, 50% of patients did not undergo annual monitoring. Other studies from different regions of the world have suggested suboptimal monitoring to be common, with rates as low as 42% reported in a German study (32) of patients initiating MTX, and <65% in a UK cohort (33) from general practitioners. A French study reported that approximately 65% of patients starting MTX underwent pre-initiation monitoring and <50% during follow-up and that more frequent monitoring led to earlier discontinuation of MTX therapy (34).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…During long-term therapy, 50% of patients did not undergo annual monitoring. Other studies from different regions of the world have suggested suboptimal monitoring to be common, with rates as low as 42% reported in a German study (32) of patients initiating MTX, and <65% in a UK cohort (33) from general practitioners. A French study reported that approximately 65% of patients starting MTX underwent pre-initiation monitoring and <50% during follow-up and that more frequent monitoring led to earlier discontinuation of MTX therapy (34).…”
Section: Discussionmentioning
confidence: 96%
“…A novel and important finding pertains to the observed suboptimal rates of laboratory monitoring, in disagreement with guideline recommendations ( 19 , 32 ). Pre-evaluation of renal, liver, and haematological parameters were lacking in 30–40% of patients newly started on MTX or biologics, and only 20–30% of patients underwent the recommended annual monitoring.…”
Section: Discussionmentioning
confidence: 99%